The impact of Dieselgate on the required rate of return on equity of VW, BMW and DAIMLER - Romana Čižinská; Pavlína Matějková; Pavel Neset (Financial Internet Quarterly, 2021)
Our paper studies the impacts of the Dieselgate scandal on the required rate of return on equity investments into VW, Daimler, and BMW. The object of investigation is the beta coefficient that determines the risk premium in the Capital Asset Pricing Model (CAPM). Our research takes a deep dive into the developments from the turning point of the scandal (the EPA NOTICE 2015) on September 18, 2015 - when a Notice of Violation of the Clean Air Act was issued to Volkswagen by the EPA - to the end of February 2016. This period also covers FORMAL COMMENCEMENT 2016, when the U.S. Department of Justice first sued Volkswagen on behalf of the EPA. The spillover (contagion) effect of fraudulent practices of VW impacted BMW, Daimler and other companies in the industry that share a similar business model and market segment. Our research of historical market betas has not confirmed the expectation that in the context of the Dieselgate scandal the return required on equity investments into VW, Daimler, and BMW would soar. The Dieselgate scandal proves that the reliability of beta estimates is an inverse function of market volatility. Historical market beta is, therefore, not a good estimate of the required rate of return for the companies in question.
Keywords: D24; G32; O12; 330; historical market beta; CAPM model; signaling theory; contagion effect; Dieselgate